Examining Circle of Security™: A Review of Research and Theory. (May 2015) - Mercer, Jean
The Circle of Security™ interventions are psychosocial treatments intended to increase maternal sensitivity and thus child attachment security in infants and young children. A small number of publications have reported empirical research on outcomes of these treatments. This article reviews the research evidence, plausibility, theoretical background, and generalizability of Circle of Security, and concludes that these interventions are plausible emerging treatments, presently weakly supported by research evidence, but potentially able to receive support from further research. The commercialization of Circle of Security is discussed as a possible obstacle to independent research. The current level of research support is described as similar to support for other interventions for young children.